Optimization of special physical fitness of sportswomen - super long distances runners by means of run training - S.I. Karaulova; L.I. Klochko (H.S. Skovoroda Kharkov National Pedagogical University, 2016)
Purpose: improvement of special physical fitness of sportswomen - super long distances runners by means of run training. Material: in the research 6 elite sportswomen of 25-27 years' age participated. We analyzed documents of training proves planning; analyzed sportswomen's diaries. Results: three cycle system of annual macro cycle's construction was put in the base of modern training system for elite marathon sportswomen. We found general and partial volumes of run load of different orientation in annual macro cycle. Optimal duration of maximal load's segments during anaerobic training was from 30 sec. to 3 minutes. Rest between segments was slow run during 3 - 8 minutes. With it, sportswomen fulfilled repeated run at segments of 15х200 m, 15х400 m, 12х600 m. Conclusions: effectiveness of system of sportswomen's special physical fitness improvement is determined by rational correlation of differently oriented run means, which were directed at increase of special fitness level in marathon.